Dry forest ants (Hymenoptera: Formicidae) of Diria National Park, Costa Rica (UNED Research Journal, 2016)
Ants are an important component on terrestrial biodiversity. It has been suggested that ant diversity increases with the complexity of the environment, and some species of ants can be used as bioindicators. We collected 1 022 ants of 46 species, and 7 subfamilies. The results suggest that some species of ants could be used as bioindicators of ecosystem alteration in the region.
Keywords: biodiversity; alteration; mirmeco wildlife; ecosystem